An In Vitro Analysis of the Effects of Intravenous Lipid Emulsion on Free and Total Local Anaesthetic Concentrations in Human Blood and Plasma. (5th November 2014) - Clark, Louise Ann; Beyer, Jochen; Graudins, Andis
Abstract : Background . Intravenous lipid emulsion (ILE) is recommended as a "rescue" treatment for local anaesthetic (LA) toxicity. A purported mechanism of action suggests that lipophilic LAs are sequestered into an intravascular "lipid-sink, " thus reducing free drug concentration. There is limited data available correlating the effects of ILE on LAs. Aims . To compare the in vitro effect of ILE on LA concentrations in human blood/plasma and to correlate this reduction to LA lipophilicity. Method . One of four LAs (bupivacaine-most lipophilic-4 mg/L, ropivacaine-6 mg/L, lignocaine-14 mg/L, and prilocaine-least lipophilic-7 mg/L) was spiked into plasma or whole blood. ILE or control-buffer was added. Plasma was centrifuged to separate ILE and total-LA concentration assayed from the lipid-free fraction. Whole blood underwent equilibrium dialysis and free-LA concentration was measured. Percent reduction in LA concentration from control was compared between the LAs and correlated with lipophilicity. Results . ILE caused a significant reduction in total and free bupivacaine concentration compared with the other LAs. Ropivacaine had the least reduction in concentration, despite a lipophilicity similar to bupivacaine. The reduction in LA concentration correlated to increasing lipophilicity when ropivacaine was excluded from analysis. Conclusion . In this first in vitro model assessing both free- and total-LA concentrations exposed to ILE in human blood/plasma, ILE effect was linearly correlated with increasing lipophilicity for all but ropivacaine.